Comparison of Islamic and Adventist Christian Eschatology - Rika Dilawati (Parahyangan Catholic University, 2022)
This study aims to discuss the comparison of life after death (exchatology) in Islam and Adventist Christianity. The research method used in this research is qualitative with the process of collecting data through literature review. The results showed that the comparison of eschatology in Islam and Christianity has a very significant difference, this can be seen in the two holy books, namely the Koran and the Bible. Eschatology in Islam is also known as the end of time or the day of judgment. Therefore eschatology is a day that is feared by every Muslim, because eschatology is a day of vengeance, where all deeds in the world will be counted on that day. While eschatology in Adventist Christianity is a day full of hope that Christians always look forward to. They waited for Christ to come a second time to take His people to the place He had prepared. However, eschatology in Islam is also shrouded in hope for salvation where Muslim belief always boils down to how big the scales of good deeds are while in this world. Therefore, this article provides great wisdom for both religions, where as religious people hope for a good place after death must always be fostered by good deeds and invite rewards as provisions later in the Hereafter.